2019
DOI: 10.1111/ppl.13013
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions of Arabidopsis thaliana MBP‐1‐like protein encoded by ENO2 in the response to drought and salt stresses

Abstract: Arabidopsis thaliana ENO2 (AtENO2) plays an important role in plant growth and development. It encodes two proteins, a full‐length AtENO2 and a truncated version, AtMBP‐1, alternatively translated from the second start codon of the mRNA. The AtENO2 mutant (eno2−) exhibited reduced leaf size, shortened siliques, a dwarf phenotype and higher sensitivity to abiotic stress. The objectives of this study were to analyze the regulatory network of the ENO2 gene in plant growth development and understand the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Eremina et al (2015) pointed that ENO2 mutants and AtMBP-1 overexpressing plants show a strong phenotypic resemblance with other mutants impaired in glycolysis, and the constitutive developmental defects in plant are correlated with a strong reduction in enolase activity, but not with a reduction in AtMBP-1 transcript abundance. Our previous study also demonstrated that AtMBP-1 is predominant in tolerance of adult Arabidopsis to abiotic stresses (Liu Z. J. et al, 2019).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Eremina et al (2015) pointed that ENO2 mutants and AtMBP-1 overexpressing plants show a strong phenotypic resemblance with other mutants impaired in glycolysis, and the constitutive developmental defects in plant are correlated with a strong reduction in enolase activity, but not with a reduction in AtMBP-1 transcript abundance. Our previous study also demonstrated that AtMBP-1 is predominant in tolerance of adult Arabidopsis to abiotic stresses (Liu Z. J. et al, 2019).…”
Section: Introductionmentioning
confidence: 68%
“…The ENO gene are widely distributed and highly conserved in vertebrates and plants which encodes a glycolytic metalloenzyme enolase (ENO2) that catalyzes the dehydration of 2-phospho-Dglycerate (2-PGA) to phosphoenolpyruvate (PEP) (Liu Z. J. et al, 2019). In Arabidopsis, there are totally three ENO genes, At1g74030 (ENO1), At2g36530 (ENO2, also referred to LOS2, Lee et al, 2002) and At2g29560 (ENO3).…”
Section: Introductionmentioning
confidence: 99%
“…The Arabidopsis pgm2 pgm3 double mutant has been reported to markedly damage the function of male and female gametophytes [ 57 ]. ENOLASE 2 (ENO2) maintains normal growth, development, and successful reproduction in plants and is also able to help plants respond to abiotic stresses such as drought and cold [ 58 , 59 , 60 ]. ENOLASE 1 (ENO1) plays a crucial role in the development of gametophytes and sporophytes [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…SA delays fruit ripening by inhibiting ethylene biosynthesis (Kumar et al, 2021; Srivastava & Dwivedi, 2000). Either increased auxin level or decreased ethylene content delays fruit ripening (Barry & Giovannoni, 2007; Liu, Zhang, et al, 2020; Sravankumar et al, 2018). Our previous research also showed that the absence of ENO2 elevated the level of auxin and decreased the ethylene content in A. thaliana seeds (Liu, Zheng, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Enolase (ENO, 2‐phospho‐ d ‐glycerate hydrolyase), a metalloenzyme in glycolysis, which catalyzes the dehydration of 2‐phospho‐ d ‐glycerate to phosphoenolpyruvate, are widely distributed and highly conserved in vertebrates and plants (Liu, Zhang, et al, 2020). There are three ENO genes in A. thaliana : AtENO1 (At1g74030), AtENO2 (At2g36530, also referred to LOS2 ) (Lee et al, 2002), and AtENO3 (At2g29560).…”
Section: Introductionmentioning
confidence: 99%